PROLONGED BRACHIAL PLEXUS BLOCKADE FOR UPPER LIMB SURGERY - O.N. YAMSHCHIKOV; A.P. MARCHENKO; S.A. EMELYANOV; O.D. IVANOVA; R.A. MARCHENKO; S.A. IGNATOVA (Avicenna Tajik State Medical University, 2023)
This article overviews the various prolonged plexus block (PB) methods. It discusses the indications and contraindications for this technique and the professional skills and equipment needed. The article also describes different approaches to a brachial plexus block (BPB): interscalene, supraclavicular, infraclavicular, and axillary. The article presents the rationale for using PB, its advantages and possible complications, and outlines the basic principles for its safe performance. Knowledge of anatomical and topographic landmarks, ultrasound navigation, and neurostimulation are utilized to determine needle position. Neurostimulation should be used to ensure the needle is placed correctly to achieve a muscle response with a current of 0.3-0.5 mA. A muscle response with a current of 0.2 mA occurs only when the needle tip is positioned intraneurally, which is unacceptable when performing plexus and nerve conduction blocks. This technique can provide prolonged anesthesia and postoperative pain relief by correctly and safely blocking nerve plexuses and trunks. It is an ideal option for anaesthesiologic support during surgical interventions and treating postoperative pain. This approach has many advantages and does not have the disadvantages associated with other types of local and general anesthesia. In this literature review, we used databases such as eLIBRARY, PubMed, and Google Scholar to search for articles related to regional anesthesia, specifically, BPB. We narrowed our search by using keywords including ultrasound navigation, neurostimulation, and catheter-based techniques.